Rethinking Civil Law Protection in Unequal Societies - Theresia N.A Narwadan (Leges Privatae, 2025)
Civil law is traditionally grounded in the assumption of formal equality among legal subjects, presuming that private autonomy and freedom of contract operate under conditions of equivalent bargaining power. In unequal societies, however, civil law relations are frequently shaped by structural disparities in economic resources, access to information, and social position. This article examines the normative foundations of civil law protection in the context of social inequality and questions the adequacy of formal equality as a basis for justice in private legal relations. Using normative juridical research with statute, conceptual, and case approaches, this study identifies normative ambiguity in civil law regarding the criteria for legally relevant inequality, the limits of restricting freedom of contract, and the consistency of legal protection across private relations. The analysis demonstrates that such ambiguity weakens legal certainty and renders civil law protection fragmented and ineffective. This article argues for a normative reconstruction of civil law protection grounded in substantive justice, treating private autonomy as a conditional principle and positioning civil law as a constitutional instrument for correcting structural inequality.